A Manajemen Nyeri Neuropati pada Pasien Diabetes Melitus Tipe 2 - Cindy Aisyah Putri Cindy Aisyah Putri (Jurnal Medika Hutama, 2021)
Neuropathic pain is pain caused by lesions on the peripheral nerves. This pain causes discomfort which decreases the sufferer's quality of life. In type 2 diabetes mellitus patients, neuropathic pain management is not as simple as that of type 1 diabetes mellitus, namely controlling blood sugar. Treatment in type 2 DM continues to be developed on specific therapies based on pain mechanisms that may differ for each individual. Pain management includes pharmacological therapy (pregabalin, gabapentin, opioids, venflaxin, etc.) as well as non-pharmacological therapy (swimming, acupuncture, physiotherapy).